Atezolizumab plus bevacizumab and chemotherapy versus bevacizumab plus chemotherapy for metastatic cervical cancer: a cost-effectiveness analysis - Cai, Hongfu; Fang, Ling; Lin, Jingwen; Zheng, Zhiwei (Frontiers in Pharmacology, 2024)
Aim The objective of this study is to conduct a cost-effectiveness analysis in order to evaluate the economic advantages of incorporating atezolizumab into a standard bevacizumab plus platinum regimen for the treatment of metastatic cervical cancer from the Chinese medical system perspective. Method We developed a partitioned survival model based on data obtained from the recently published BEATcc clinical trial and economic cost data. Our model utilized a tree-based decision analysis approach to simulate two different treatment strategies for metastatic cervical cancer: the standard bevacizumab plus platinum regimen, and the addition of atezolizumab to the standard treatment regimen. The economic assessment data included the costs of the drugs, costs related to treatment-induced adverse events. The cost-effectiveness metrics used in the analysis were quality-adjusted life-year (QALY) and incremental cost-effectiveness ratio (ICER). The robustness of our model was assessed through sensitivity analysis. Result The total costs of the atezolizumab group were 128179.56, while the costs of chemotherapy group were 42065.89. The atezolizumab group gained 3.52 QALYs, whereas the chemotherapy group gained 2.35 QALY. The atezolizumab regimen resulted in an increase of 1.17 QALYs at an incremental cost of 86113.67. This led to an ICER of 73601.43, which exceeds the willingness-to-pay (WTP) threshold of 39855.79 in China. Sensitivity analysis demonstrated none of the parameters within a margin of ±25% result in significant alterations to the analysis findings. Conclusion Atezolizumab plus bevacizumab and chemotherapy was not to be a cost-effective option for the treatment of metastatic cervical cancer compared to bevacizumab plus chemotherapy.